Pengaruh Pengenaan Value Added Tax Pada Top-Up Game Online Terhadap Keputusan Pembelian Konsumen - Alvaro, Rakan; Meliana Desiani Christanto, Meliana Desiani Christanto (Jurnal Paradigma Ekonomika, 2025)
Rapid technological advancements, particularly in the digital entertainment sector, have boosted the popularity of online gaming in Indonesia. Along with that, top up transactions for the purchase of virtual goods have increased, contributing significantly to the gaming industry. To make sure top up transactions contribute to the Indonesia, the government imposes Value Added Tax. However, the VAT imposition on these transactions has caused impacts on consumer’s purchasing decisions because it increases price of top ups. This study aims to analyze effect of VAT imposition on online game top-up transactions on purchasing decisions. Using quantitative descriptive method with simple linear regression, data were obtained through questionnaires from 100 respondents selected by purposive and accidental sampling. This study results showed that the imposition of VAT caused significant influence on purchasing decisions, with variable (VAT) contribution of 82.8%, while 17.2% is from other factors. This research provides insights how VAT affects top up purchase decisions.